Use of Artificial Intelligence in Market Intelligence System - Kumar, Shiv; Jhajhria, Abimanyu; T, Kingsly Immanuelraj (Indian Farming, 2019)
Implementation of GPS enabled new signals to enhance the quality, as well as efficiency of agricultural operations, and thereby, increase the overall productivity in future. The major problem is that the environment of Artificial Intelligence (AI) is not exactly the same as farmers’ field which makes the testing, validation and successful rollout of AI and other related (Industry 4.0 revolution) technologies much more riskier and laborious than in other industries. Sometimes the cost associated with implementation of AI in agriculture becomes so high and unaffordable due to unpredictability associated with each and every aspect of agriculture such weather, pests, soil, etc. Increasing consumption and rising requirement of better yield are estimated to be one of the major factor that is fueling the demand of automating farming operations. The farmers want to shift more towards automation to enhance yield and improve the product quality. This technology assist farmers in enhancing their crop yield and product quality by analyzing and correlating large amount of structured and unstructured data from multiple sources to extract actionable insights to enhance yield.